A theoretical framework for studying the co-creation of innovative solutions and public value. (1st April 2021) - Torfing, Jacob; Ferlie, Ewan; Jukić, Tina; Ongaro, Edoardo
Abstract : The expansion of the scope and significance of co-creation in public policy and governance prompts the integration of different theoretical strands that together can help us illuminating the antecedent conditions, the processes of multi-actor collaboration, the creation of innovative solutions, and the assessment of their public value. Exploring the affinities and complementarities of relevant perspectives such as theories of co-creation, public value management, public innovation, collaborative governance, network governance, strategic management and digital era governance may foster a more comprehensive framework for studying the co-creation of public value outcomes such as needs-based services, effective governance and democratic legitimacy. This introduction seeks to explain why we must transform the public sector in order to spur co-creation, how strategic management and digital platforms can support this transformation, and why we must bring together and synthesize different bodies of theory when studying the complex processes of co-creation and their drivers, barriers and outcomes.